Şamlı bir sûfî: Şeyh Arslan Dımaşkî ve Tevhîd Risâlesi - (:unkn) unknown (My University, 2010)
Şeyh Arslan Dımaşkî, tarîkatların oluşum döneminde tevhîd anlayışı üzerine önemli bir eser vermiş Şamlı sûfîlerdendir. İsminden de anlaşılacağı üzere kendisi Türk asıllıdır. Ayrıca Tevhîd Risâlesi pek çok şerhe konu olmuştur. Eser şirk-i hafî, yakînî iman, şerîat ve hakîkat, süluk makamları, fenâ, ihlâsın dereceleri, muhabbet gibi konuları ele alır. Müellif ve eseri ülkemizde yeterince tanınmadığı için bu makalede, Şeyh Arslan’ın hayatı, eserleri ve önemi hakkında bilgi verilmeye çalışılacaktır. Ayrıca makalenin sonunda Tevhîd Risâlesi’nin tercümesi verilecek, böylece bu önemli sûfînin tasavvuf araştırmacılarına tanıtımına katkıda bulunulacaktır.

Sheikh Arslan of Damascus is one of the important sufis who has written on the subject of tawhid, unity of God, during the formative period of the Sufi orders. As understood from his name, he comes from Turkish origins, [the word “Arslan” means lion in Turkish]. Although his work is very concise, there have been many commentaries written about it due to its significance. The epistle deals with the hidden polytheism, faith with certainty, shari’ah and the Truth, the stations of the Sufi path, annihilation in God, the degrees of sincerity, and love for God. Because the author and his work are not well-known in this country, we will try to present some information about Sheikh Arslan’s life, works, and their significance. In order to introduce this important Sufi to the researchers, we have also added the Turkish translation of his epistle at the end of our article.
Sheikh Arslan Damascus and his Episte on Tawhid
Keywords: Din Bilimi